Electrical Discharge Machining (EDM) untuk Manufaktur Presisi Orifice Nozzle Injector Mesin Diesel: Sistematik Review Kemajuan, Optimalisasi, Dan Keberlanjutan - Irwan Sukma; Ghany Heryana (Jurnal Teknologi dan Rekayasa Alat Berat, 2026)
Electrical Discharge Machining (EDM) has evolved from a non-conventional machining process into a critical high-precision manufacturing technology for advanced materials. This paper presents a systematic review of recent developments in EDM technology based on an analysis of research articles published between 2019 and 2025. The review focuses on four main areas: (1) process parameter optimization using intelligent methodologies such as swarm intelligence, machine learning, and Response Surface Methodology (RSM); (2) innovations in hybrid processes, including Powder-Mixed EDM (PMEDM), ultrasonic and magnetic field-assisted EDM, and the use of electrolytic-dielectrics to produce defect-free surfaces; (3) developments in electrode materials and the machining of advanced alloys like titanium alloys, Shape Memory Alloys (SMAs), and magnesium alloys; and (4) sustainability trends in EDM through the use of environmentally friendly dielectrics and environmental impact minimization. The synthesis indicates that EDM research is moving towards smarter, more efficient, multifunctional (via surface modification), and sustainable processes. This review concludes by highlighting existing challenges and providing suggestions for future research directions.